Tinjauan Yuridis Over Kredit Rumah Bersubsidi Berdasarkan Permen PUPR Nomor 21/Prt/M/2019 - Sari, Ika Kartika; Givari, Ahmad Geis (Universitas Cokroaminoto Yogyakarta, 2024)
in practice, there are often overcredit transactions without the bank's approval, which has the potential to cause legal conflicts. The government through the Regulation of the Minister of Public Workers and Public Housing (PUPR) No. 20/PRT/M/2019 has regulated the mechanism for subsidized housing loans. This research uses a qualitative method with an empirical juridical approach, using primary data (observations, and interviews), secondary data (books, journals, scientific papers, laws, etc.) tertiary data sources (dictionaries, websites, and others). The results of the study show that in Cirebon Regency there are still violations due to lack of public understanding and weak supervision. Therefore, there is a need for more strict socialization of regulations and law enforcement to ensure that over-credit runs in accordance with its provisions.